PENGARUH VENUE PADA EVENT SAWAHLUNTO INTERNATIONAL SONGKET SILUNGKANG CARNAVAL TERHADAP MEMORABLE TOURISM MELALUI REVISIT INTENTION - Afrilian, Pepy; Veronika, Widya; Silvandi, Givara Oksafa (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
AbstractThe city of Sawahlunto, West Sumatra actively promotes its cultural, artistic, and local heritage through the Sawahlunto International Songket Silungkang Event. This event is intriguing to study as it utilizes public streets, which also serve as a cultural heritage site reflecting the historical legacy of Minangkabau. The selection of an appropriate venue in implementing an event plays a significant role in creating memorable tourism experiences. This research incorporates the variable of revisit intention, representing the desire to witness an event repeatedly, as a mediator between the influence of the venue and memorable tourism. Employing a quantitative method with path analysis, the study aims to explore the direct and indirect effects of the venue on memorability through revisit intention. Questionnaires were distributed to 99 respondents using probability sampling, and data were processed using the IBM SPSS version 22 programming system. After data analysis, the research findings indicate no direct influence among the variables studied. Consequently, the indirect impact of the venue on memorable tourism through revisit intention also suggests no significant effect. This implies that the revisit intention variable does not act as a mediator in connecting the relationship between the venue and memorable tourism.Keywords: Revisit Intention; Memorable Tourism; Tourist Experiences; Event Venue; Cultural EventAbstrakKota Sawahlunto mendorong promosi budaya, kesenian, dan warisan lokal menggunakan Event Sawahlunto Internasional Songket Silungkang. Event ini menarik dibahas karena vanue yang digubakan adalah jalanan umum yang juga cagar budaya peninggalan sejarah/kota tua nya Minangkabau untuk itu, pemilihan venue (lokasi atau tempat) yang tepat dalam pelaksanaan sebuah event berperan menciptakan sebuah kenangan atau memorable tourism oleh wisatawan. Penelitian ini juga menggunakan variable revisit intention atau keinginan menyaksikan event secara berulang sebagai perantaara antara pengaruh vanue dengan memorable tourism. Penelitian menggunakan metode kuantitatif dengan teknik analisis jalur untuk mengetahu pengaruh langsung dan tidak langsung venue terhadap memorable melalui revisit intention. Dengan menyebarkan kuisioner kepada 99 responden dengan teknik probability sampling dan pengolahan data yang menggunakan system pemograman IBM SPSS versi 22, setelah melalui tahap pengolahan data maka didapati hasil penelitian tidak adanya pengaruh secara langsung antarvariable penelitian. Sehingga pengaruh secara tidak langsung venue terhadap memorable tourism melalui revisit intentionjuga mendapati hasil tidak adanya pengaruh atau dapat dikatalan variabel revisit intention tidak memiliki peran sebagai penghubung antara hubungan venue dengan memorable tourism.Kata Kunci: Revisit Intention; Memorable Tourism; Tourist Experiences; Event Venue; Event Budaya